JURNALISME SENSITIF BENCANA DALAM MANAJEMEN PENCARIAN, PENGELOLAAN INFORMASI DAN PEMBERITAAN BENCANA DI RUANG REDAKSI - Filosa Gita Sukmono; Fajar Junaedi (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2018)
The real experience of journalists in the field when disaster coverage is learning that can be researched empirically  in disaster coverage in the present and future. The purpose of this research described problems communication disaster experien ced by reporters at the disaster, within specific research about experiences journalist who served in Yogyakarta and surrounding when coverage eruption Merapi 2010. Methods used in this research is indepth interviews with the journalists who involved in disaster coverage. The result of this research was found an important aspect that must be controlled reporters, namely, the ability accuracy and verification of data in coverage that puts forward journalism sensitive disasters and as well as to give hope to residents affected disaster and people through journalism optimistic in disaster coverage. The absence of standard operating procedure (SOP) of disaster coverage during the eruption of Merapi Mount eruption in 2010 became a valuable lesson for various media. The SOP of disaster coverage becomes significant in disaster coverage which now has to be prepared by the editor before giving assignments to journalists to cover the disaster. This research contributes to give a new insight for journalist on disaster journalism issue.